Potential of Fecal-Oral Transmission and Gastrointestinal Manifestation of COVID-19 - Randy Adiwinata; Visakha Revina Irawan; Jonathan Arifputra; Bradley Jimmy Waleleng; Fandy Gosal; Luciana Rotty; Jeanne Winarta (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
The World Health Organization have declared COVID-19 as a pandemic. The COVID-19, caused by SARS-CoV-2, is spreading at an alarming rate and creates a significant worldwide burden to the economy while increasing morbidity and mortality. While COVID-19 was primarily considered as a respiratory-infection disease, several reports have shown that many COVID-19 infected patients have presented or developed some digestive symptoms. Many studies also demonstrated, using reverse transcriptase-polymerase chain reaction method, that SARS-CoV-2 are present in stools or other gastrointestinal tract secretions. All these reports raised the possibility of COVID-19 transmission via the fecal-oral route and the involvement of the gastrointestinal-liver system. Until further studies are available, physicians should be aware of the digestive manifestation of COVID-19 and use universal precautions to avoid the transmission of COVID-19 via the fecal-oral route.